The genesis of Islamic finance system: Exploring the mainsprings and emerging markets - Athar Shahbaz Wani (International Journal of Financial, Accounting, and Management, 2022)
Purpose: The present paper aims in-depth analysis of the Islamic Banking and Finance Industry (IBFI) in relation to its emergence, consolidation, and impact on the geo-economic scenario.  With this, the Emerging Markets of Islamic Finance in several jurisdictions are highlighted to indicate the global influence of IBFI in the contemporary economic scenario.  Research Methodology: The methodology in the research will be altogether qualitative, involving descriptive and analytical methods. Results: The analysis finds that unprecedented developments engulfing the Middle East post-1970s like, the pan-Islamism oil embargo of 1973-1974, played a pivotal role in materializing the emergence of Islamic Banking and Finance theory into a ‘viable corporate system. Limitations: The paper as such is not the statistical overview of IBFI in its sectors of intermediation like Islamic Banking. Islamic Insurance (Takaful), Islamic Capital Market, etc. The paper also doesn’t evaluate the internationalization and standardization aspects of  IBFI. Contribution: The discussion in the manuscript will develop a coherent understanding of the emergence, growth, and development of IBFI in the contemporary geo-economic scenario. Moreover, the analysis in the paper establishes the emergence of IBFI as a global phenomenon, and thus explores the possibilities of further research in several aspects/sectors of IBFI Islamic Banking. Islamic Insurance (Takaful), Islamic Capital Market.